Fresno County Bar Association Law Day Luncheon with Robert McConnell - Watkins, Howard::::::::: (1984)
Howard Watkins presenting Legal Services Pro Bono Attorney Award to William Ninnis; seated: Brad Hill and Stan Cardenas; back of Judge Blaine Pettitt's head Main ballroom of The Fresno Hilton Hotel